Hierarchical Porous LiNi1/3Co1/3Mn1/3O2 nano-/micro spherical cathode material : minimized cation mixing and improved Li+ mobility for enhanced electrochemical performance - Chen, Zhen (2018)
Although being considered as one of the most promising cathode materials for Lithium-ion batteries (LIBs), LiNi1/3Co1/3Mn1/3O2 (NCM) is currently limited by its poor rate performance and cycle stability resulting from the thermodynamically favorable Li+/Ni2+ cation mixing which depresses the Li+ mobility. In this study, we developed a two-step method using fluffy MnO2 as template to prepare hierarchical porous nano-/microsphere NCM (PNM-NCM). Specifically, PNM-NCM microspheres achieves a high reversible specific capacity of 207.7 mAh g−1 at 0.1 C with excellent rate capability (163.6 and 148.9 mAh g−1 at 1 C and 2 C), and the reversible capacity retention can be well-maintained as high as 90.3% after 50 cycles. This excellent electrochemical performance is attributed to unique hierarchical porous nano-/microsphere structure which can increase the contact area with electrolyte, shorten Li+ diffusion path and thus improve the Li+ mobility. Moreover, as revealed by XRD Rietveld refinement analysis, a negligible cation mixing (1.9%) and high crystallinity with a well-formed layered structure also contribute to the enhanced C-rates performance and cycle stability. On the basis of our study, an effective strategy can be established to reveal the fundamental relationship between the structure/chemistry of these materials and their properties.